2018
DOI: 10.7554/elife.34338
|View full text |Cite
|
Sign up to set email alerts
|

Synapse-specific and compartmentalized expression of presynaptic homeostatic potentiation

Abstract: Postsynaptic compartments can be specifically modulated during various forms of synaptic plasticity, but it is unclear whether this precision is shared at presynaptic terminals. Presynaptic homeostatic plasticity (PHP) stabilizes neurotransmission at the Drosophila neuromuscular junction, where a retrograde enhancement of presynaptic neurotransmitter release compensates for diminished postsynaptic receptor functionality. To test the specificity of PHP induction and expression, we have developed a genetic manip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
76
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(80 citation statements)
references
References 95 publications
(165 reference statements)
3
76
1
Order By: Relevance
“…Previous work demonstrated that the fast expression of PHP in response to PhTx occurs even when the motor neuron axon is severed (Frank et al, 2006). Also, the signaling necessary for PHP expression is restricted to postsynaptic densities and presynaptic boutons (Li et al, 2018). Second, Neto-CTD, but not Neto-β, rescued the basal neurotransmission defects in neto-α null (Figures 6 and 8).…”
Section: Discussionmentioning
confidence: 89%
“…Previous work demonstrated that the fast expression of PHP in response to PhTx occurs even when the motor neuron axon is severed (Frank et al, 2006). Also, the signaling necessary for PHP expression is restricted to postsynaptic densities and presynaptic boutons (Li et al, 2018). Second, Neto-CTD, but not Neto-β, rescued the basal neurotransmission defects in neto-α null (Figures 6 and 8).…”
Section: Discussionmentioning
confidence: 89%
“…Together, these results demonstrate that inc functions downstream of or in parallel to CaMKII in 224 the postsynaptic compartment, where it is necessary for the retrograde homeostatic signaling 225 that adaptively modulates presynaptic structure and neurotransmitter release (schematized in 226 Fig. 3)), suggesting that the key processes driving synapse-250 specific retrograde PHP signaling occur in this structure (Li et al, 2018b). We therefore first 251 determined whether Inc is present at the postsynaptic density.…”
Section: Inc Functions Downstream Of Camkii or In A Parallel Pathway mentioning
confidence: 95%
“…Retrograde PHP signaling involves multiplexin/ endostatin (Wang et al, 2014) and Sema-2B/Plexin B (Orr et al, 2017). PHP requires postsynaptic mTOR signaling (Goel et al, 2017;Penney et al, 2012), class II PI3 kinase function (Hauswirth et al, 2018), and reduced pCaMKII levels (Goel et al, 2017;Li, Goel, Chen, et al, 2018;Newman et al, 2017). Note that the cartoon only summarizes recent genes implicated in PHP.…”
Section: Physiology and Genesmentioning
confidence: 99%
“…Unc18 or GFP-tagged Cacophony (Gratz et al, 2019;Li, Goel, Chen, et al, 2018), implying a sustained increase in the levels of these proteins during PHP. In this case, three of the above-mentioned genes that have been tested for PHP in the GluRIIA SP16 mutant background-cacophony (Frank et al, 2006), Brp Penney et al, 2012), and Srpk79D ( (2019), Arl8-dependent structural plasticity was dispensable for rapid PHP expression, but required for sustained PHP expression.…”
Section: Active Zone Structurementioning
confidence: 99%
See 1 more Smart Citation